VD_FINDINFO Jug / 2024 / 553 vom 1. Januar 2021 - VD Tribunal cantonal (2021)
RESPONSABILITÉ DE L'EMPLOYEURAVS, CERTIFICAT DE TRAVAIL, TORT MORAL, HARCÈLEMENT PSYCHOLOGIQUE | 28 CO, 328 CO, 330a al. 1 CO, 47 LPers-VD, 5 al. 3 LPers-VD